Outcome Prediction in Acute Stroke Patients by Continuous Glucose Monitoring. Issue 8 (12th April 2018) - Wada, Shinichi; Yoshimura, Sohei; Inoue, Manabu; Matsuki, Takayuki; Arihiro, Shoji; Koga, Masatoshi; Kitazono, Takanari; Makino, Hisashi; Hosoda, Kiminori; Ihara, Masafumi; Toyoda, Kazunori
Abstract : Background: The purpose of this study was to examine the relationships between glucose parameters obtained by continuous glucose monitoring and clinical outcomes in acute stroke patients. Methods and Results: Consecutive patients with acute ischemic stroke or intracerebral hemorrhage within 24 hours after onset were included. A continuous glucose monitoring device (iPro2) was attached for the initial 72 hours after emergent admission. Eight glucose parameters were obtained from continuous glucose monitoring: maximum, minimum, mean, and SD of blood glucose levels, as well as area under the curve more than 8 mmol/L of blood glucose, distribution time more than 8 mmol/L of blood glucose, coefficient of variation (%CV), and presence of time less than 4 mmol/L over 72 hours. The primary outcome measure was death or dependency at 3 months (modified Rankin Scale score ≥3). One hundred patients with acute ischemic stroke (n=58) or intracerebral hemorrhage (n=42) were included. Blood glucose levels varied between 5.2±1.4 and 11.4±3.2 mmol/L over 72 hours, with area under the curve more than 8 mmol/L of blood glucose of 0.7±1.4 min×mmol/L, distribution time more than 8 mmol/L of blood glucose of 31.7±32.7%, coefficient of variation of 15.5±5.4%, and presence of hypoglycemia in 20% of overall patients. Mean glucose level (adjusted odds ratio, 1.60, 95% confidence interval, 1.12–2.28/1 mmol/L), area under the curve more than 8 mmol/L of blood glucose (2.13, 1.12–4.02/1 min×mmol/L), and distribution time more than 8 mmol/L of blood glucose (1.25, 1.05–1.50/10%) were related to death or dependency for overall patients, as well as for acute ischemic stroke patients (2.05, 1.15–3.65; 2.38, 1.04–5.44; 1.85, 1.10–3.10, respectively). Conclusions: High mean glucose levels, distribution time more than 8 mmol/L of blood glucose, and areas under the curve more than 8 mmol/L of blood glucose during the initial 72 hours of acute stroke were associated with death or dependency at 3 months.